Optimizing Toluene Inventory Control Using Economic Order Quantity - Muhammad Nabil Arijuddin; Siti Rahayu; Andini Putri Riandani (Universitas Panca Marga, 2026)
Raw material inventory control plays an important role in maintaining production continuity and reducing inventory costs. CV. AK INDOPRIMA, a thinner manufacturing company, still determines the quantity and timing of Toluene raw material orders based on estimation. This condition causes inventory fluctuations, including overstock in several periods and shortage risk in other periods. This study aims to analyze the company’s current inventory control system and determine an optimal inventory policy using the Economic Order Quantity (EOQ) method, supported by Safety Stock, Reorder Point (ROP), and Total Inventory Cost (TIC) calculations. This study used a quantitative descriptive method. Data were collected through observation, interviews, and company documentation for the January to December 2025 period. The results showed that the annual demand for Toluene was 183,600 liters. The EOQ calculation produced an optimal order quantity of 5,777.70 liters per order, with an ordering frequency of 32 times per year or every 9 days. The Safety Stock was 2,799 liters, while the Reorder Point was 5,859 liters. The Total Inventory Cost based on the EOQ policy was IDR 63,554,796 per year. These results indicate that the integrated EOQ-based policy can provide a more structured inventory control system by determining order quantity, safety inventory, reorder timing, and annual inventory cost. From a managerial perspective, the proposed policy can help managers reduce subjective purchasing decisions, establish a measurable ordering schedule, prevent excessive stock accumulation, reduce shortage risk, and maintain the availability of Toluene raw material to support production continuity at CV. AK INDOPRIMA.